Panax notoginseng saponins protect PC12 cells against Aβ induced injury via promoting parkin-mediated mitophagy. (1st March 2022) - Jiang, Yixuan; Li, Hemei; Huang, Panling; Li, Shanliang; Li, Bocun; Huo, Lini; Zhong, Jing; Pan, Ziyu; Li, Yuqing; Xia, Xing
Abstract: Ethnopharmacological relevance: Panax notoginseng (Burk) F. H. Chen is a well-known traditional Chinese medicine with a long history and is widely used in the treatment of cerebrovascular disease. Panax notoginseng saponins (PNS) are the main active ingredients in Panax notoginseng (Burk) F. H. Chen, and its injection is used to treat nerve damage caused by cerebral ischemia and other conditions. PNS is thought to alleviate cognitive impairment in patients with Alzheimer's disease; however, its mechanism of action is unclear. Aim of the study: We elucidated the role of PNS in attenuating cellular mitochondrial damage caused by amyloid β (Aβ) protein and in protecting cell viability from the perspective of regulating autophagy. By investigating the effects of PNS on the targets regulating mitophagy, we wanted to reveal the autophagy related mechanism by which PNS attenuated Aβ damage in neuronal cells. Materials and methods: The effect of PNS on the mitochondrial membrane potential of Aβ-injured PC12 cells was detected using flow cytometry, which reflected the alleviating effect of PNS on mitochondrial damage. Using mRFP-GFP-LC3-transfected PC12 cells, the effect of PNS on cellular autophagy flux was observed using laser confocal microscopy. Formation of the intracellular autophagosome was observed using transmission electron microscopy, which reflected the activation of autophagy by PNS. The siPINK1 lentivirus was used to silence the PINK1 gene in PC12 cells to obtain siPINK1-PC12 cells. The effects of PNS on the expression of the PINK1 gene and on the autophagy-related proteins LC3II/Ⅰ, p62, PINK1, parkin, NDP52, and OPTN were observed to reveal the possible targets of PNS in regulating autophagy. Results: After PNS treatment, the viability of Aβ-injured PC12 cells improved and the mitochondrial membrane potential was restored. PNS treatment significantly enhanced the autophagy flux of damaged cells and increased the levels of LC3II/Ⅰ protein and decreased p62 protein, while significantly improving the structure and mitochondrial morphology of PC12 cells injured by Aβ. These changes led to more autophagosomes wrapping around the damaged mitochondria and promoting the depletion of OPTN, a mitophagy receptor. After silencing the PINK1 gene, PNS could not alter the PINK1 gene and protein levels, but could still increase LC3II/Ⅰ, decrease p62 and OPTN, and significantly increase the amount of parkin. Conclusions: PNS could enhance the autophagic activity of cells, alleviate mitochondrial damage caused by Aβ injury, and protect the activity of PC12 cells. It is possible that enhanced autophagy was achieved by promoting the recruitment of parkin protein to the mitochondrial receptors in a non-PINK1-dependent manner. Graphical abstract: Image 1 Highlights: PNS protects Aβ-injured PC12 cells, along with mitophagy activation. PNS promotes mitophagy through a non-PINK1-dependent manner. Increasing parkin is an important mechanism for the neuroprotective effect of PNS.